Stress Appraisal, Stress Mindset, and Perceived Pain During a Cold Pressor Test. - Tse, Helen Wing Yuk; Hanssen, Marjolein M.; Vancleef, Linda M. G.; Peters, Madelon L. (International Journal of Behavioral Medicine, 2026)
Background: Previous studies demonstrated that task-specific stress appraisals as well as the more general belief that stress is (mal)adaptive (i.e., stress mindset) can affect the stress response. Little is known about the influence of stress appraisals and stress mindset on pain perception. The current study investigated whether stress appraisals and/or stress mindset moderates the impact of stress on pain perception. Method: Sixty participants performed a stress-inducing speech preparation task followed by the cold pressor test (CPT) to induce pain. Threat appraisal of the speech task was measured with a questionnaire. Stress mindset was manipulated with a video clip emphasizing either the debilitating or enhancing nature of stress, after which another administration of the CPT took place. Results: Participants in the "stress-is-enhancing" condition reported less pain on the second CPT than on the first, while participants in the "stress-is-debilitating" condition demonstrated similar pain levels. There was no effect of threat appraisals of the speech task on pain perception. Conclusion: These findings provide evidence on the impact of stress mindset on pain perception. Future studies could extend these findings to patients with pain and examine whether mindset interventions can be a useful component in pain management.